PENGARUH PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS V DI SD NEGERI WAIKARYA - Dena, Kristian Mone (Al-Alam: Islamic Science Education Journal, 2025)
This research was conducted with the following objectives: (1) To determine the effect of using the Discovery Learning learning model on the achievement of science learning outcomes in fifth grade students of Waikarya State Elementary School; (2) To determine the differences in science learning outcomes between students who are taught using the Discovery Learning learning model and students who use the conventional learning model. The research method used was a quantitative approach with a quasi-experimental design, namely using the Nonequivalent Control Group Design pattern. Data collection techniques were carried out through tests and documentation, while data analysis used bivariate analysis to identify significant differences in averages. The research instrument was a science learning outcome test given at the pretest and posttest stages. The analysis results using the Mann-Whitney U test showed U = 0.000, Z = -6.348, with an Asymp. Sig. (2-tailed) value of 0.000 < α = 0.05, so the hypothesis was accepted. With df = 24 (N-2), the r table value was 0.404, which strengthens the finding of a significant difference in learning outcomes. Conclusion of research findings, it can be concluded that (1) the use of the Discovery Learning model has a positive and significant influence on the science learning outcomes of fifth grade students; (2) there is a real difference in science learning outcomes between the experimental group and the control group. The results of the Mann-Whitney U test show a significance value <0.05 and are supported by a comparison of the r table (0.404) with statistical results. Thus, student learning outcomes in classes using Discovery Learning are higher than those in classes using conventional learning, so it can be concluded that the Discovery Learning model is more effective to implement.